High Capacity Broadband: An Economic, Environmental and Social Imperative for 2009. - Bryce, Mal (2009)
This discussion paper outlines the tangible economic, environmental and social benefits associated with the provision of high capacity broadband infrastructure. It also provides the context in which the current debate about network speeds has developed. Whilst it is recognized that there are certain contentious difficulties associated with the arrival of this new infrastructure it was a conscious decision by the author to allow others to elaborate upon this aspect of the debate. The word imperative implies a sense of urgency. It is the author’s view that the magnitude of the challenge in 2009 to recover from the current global economic meltdown and to create a carbon neutral future clearly establishes that sense of urgency. For the purposes of this paper, high capacity broadband is defined as the level of communications capacity to a single dwelling or commercial unit that is capable of delivering contemporary entertainment and communications services to the occupants. In the near future this will mean several IPTV channels and multiple simultaneous high definition video phone calls. For technology that will arrive in the next few years 50 -100 Mbps will constitute high capacity broadband. Serious bandwidth in telecommunications has only been a matter of real and growing significance for the last ten years Technological breakthroughs in recent decades have changed fundamentally the scope and nature of services provided by telecommunications carriers. In the late 1990’s normal household access speeds to the Internet in Australia were in the range of 128-256 Kbps. By 2007 the majority of Australian’s were enjoying connection speeds above 1.5 Mbps. Globally, many communities are already enjoying connections speeds of 20-30 Mbps and developing infrastructure for speeds of up to 100Mbps. Connection speeds seem to be doubling every 15-18 months. Designing and building the “hard” telecommunications infrastructure is the foundation upon which a contemporary connected community can be established. Providing “soft” infrastructure is however the most important step in delivering a resilient future, global competitiveness, sustainability, strong community capacity and a real return on investment in telecommunications hardware. Global and local competitiveness will ultimately depend upon the genius and creativity applied to harnessing the power of high capacity broadband.